HUBUNGAN ANTARA FEAR OF MISSING OUT DENGAN SELF CONTROL PADA PESERTA DIDIK PENGGUNA MEDIA SOSIAL TIKTOK - fitri, Nur Fitria; Muryono, Sigit (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2024)
This research was inspired by research findings in the educational environment during the 3 month introduction to school among students. So far, researchers have observed that many students use gadgets to open the TikTok application, both in class and outside of class. This investigation aims to show the relationship between the level of fear of missing out and self-control in grade 8 students who use TikTok as their main social media at SMPN 103 Jakarta. The research methodology is quantitative correlational with a population of 360 students. The sample taken consisted of ninety class VIII students, taken randomly. The data collection method uses a questionnaire containing strong and weak options. The tool whose validity was tested showed 48 valid items out of 56 items for fear of missing out and 42 valid items out of 48 items related to the self-regulation variable used to test the validity of the scale. There is an alpha value of 0.976 for Fear of Missing Out and Self-Control on the Cronbach Scale, and an alpha value of 0.940 for the test which is considered very reliable. Additionally, the analysis terms were tested for normality with the Kolmogorov-Smirnov formula. The results show a normal distribution. Followed by the results of the linearity test. The value (r) of 0.309 produced by the Pearson Product Moment correlation coefficient formula with a significance level of 0.00–0.005 indicates that there is a significant positive relationship between fear of loss and the dependent variable of self-control for Class VIII students. That is, the greater the fear of missing out, the more control over oneself, and conversely, the lower the fear of missing out, the less control over oneself.